Promotion of Indian Languages Literature in Web by applying Natural Language Processing - Ranjan Jena, Amrut; Kumar Sinha, Mohit; Raj, Yash; Raj, Rikesh; Kumari, Shivani; Singh, Alka; Kumar, Nitish (International Journal of Computer Sciences and Engineering, 2026)
With the aid of natural language processing, this study seeks to develop a web application that will promote, protect, and highlight India's literary heritage as well as the value of its languages. The application offers an interactive user experience that is visually beautiful and welcoming. It features a database exhibiting the many Indian languages, as well as information on their background, cultural importance, and important literary productions. Users can browse language-specific areas, use interactive maps to navigate, access language study tools, join in forums tailored to their language, and take part in virtual literary events. Overall, the website acts as a thorough platform for celebrating and learning about India's rich literary heritage and linguistic variety.